Development of a low-cost quadrotor UAV based on ADRC for agricultural remote sensing - Zhang, Songchao; Xue, Xinyu; Chen, Chen; Sun, Zhu; Sun, Tao (International Journal of Agricultural and Biological Engineering, 2019)
Unmanned aerial vehicle (UAV) has the advantages of good repeatability and high remote sensing (RS) information acquisition efficiency, as an important supplement bridging the gap of high-altitude and ground RS platforms. A quadrotor UAV was developed for the agricultural RS application in this study. The control system consists of a main processor and a coprocessor, integrating a three-axis gyroscope, a three-axis accelerometer, an air pressure sensor and a global positioning system (GPS) module. Engineering trial method (ETM) was used to tune the parameters based on the active disturbance rejection control (ADRC) method. Also a ground control station (GCS) adapted to the quadrotor was developed realizing autonomously take-off and landing, flight route planning, data recording. To investigate the performances of the UAV, several flight tests were carried out. The test results showed that the pitch angle control accuracy error was less than 4°, the flight height control accuracy error was less than 0.86 m, the flight path control accuracy error was less than 1.5 m overall. Aerial multispectral images were acquired and processed. The reflected digital number (DN) values obtained from a height of 10-100 m with 10 m interval could be referenced to classify objects. The normalized-difference-vegetation index (NDVI) values obtained from the aerial multispectral images acquired at 15 m were compared with those obtained by the GreenSeeker (GS) and PSR-1100F. The maximum error was 20.37% while the minimum error was 1.99%, which demonstrated the developed quadrotor UAV’s satisfactions for low altitude remote sensing practice. This study provided a low-cost platform for agricultural remote sensing.Keywords: UAV, quadrotor, ADRC, agricultural remote sensing, NDVI, aerial spraying applicationDOI: 10.25165/j.ijabe.20191204.4641Citation: Zhang S C, Xue X Y, Chen C, Sun Z, Sun T. Development of a low-cost quadrotor UAV based on ADRC for agricultural remote sensing. Int J Agric & Biol Eng, 2019; 12(4): 82–87.